Splenectomy and removal of bilateral huge chocolate cyst with ovarian preservation - Gurung, G; Rana, A; Joshi, P; Pradhan, P (Journal of Institute of Medicine Nepal, 2007)
Case report: An unusual discovery of exceptionally large, bilateral chocolate (endometriotic) cysts of ovaries amidst dense pelvic adhesion and thick peritoneal collection due to occasional spill from the cyst in a young adolescent, encountered during spleenectomy performed for idiopathic thrombocytopenia is reported. Key words: Chocolate cysts, ovarian cyst, spleenectomy, thrombocytopaenia The full text of this paper is available at Journal of Institute of Medicine website